Molecular cloning and functional identification of an apple flagellin receptor MdFLS2 gene - Chen-hui QI; Xian-yan ZHAO; Han JIANG; Hai-tao LIU; Yong-xu WANG; Da-gang HU; Yu-jin HAO (Journal of Integrative Agriculture)
The leucine-rich repeat receptor kinase flagellin-sensing 2 gene (MdFLS2; Gene ID: MDP0000254112) was cloned from Royal Gala apple (Malus×domestica Borkh.). This gene contained a complete open reading frame of 3474 bp that encoded 1158 amino acids. The phylogenetic tree indicated that Prunus persica FLS2 exhibited the highest sequence similarity to MdFLS2. The PlantCare database suggests that the promoter sequence of MdFLS2 contains several typical cis-acting elements, including ethylene-, gibberellin-, salicylic acid-, and drought-responsive elements. Quantitative real-time PCR analysis showed that MdFLS2 was widely expressed in the different tissues of the apple and most highly expressed in the leaves. Furthermore, MdFLS2 was significantly induced by the flagellin elicitor peptide flg22. Treatment of the apple seedling leaves with flg22 resulted in an increase in leaf callose levels with increased treatment duration. An increase in the production of O2– along with the expression of disease-related genes was also observed. An oxidative burst was detected in the treated seedlings, but not in the control seedlings, indicating that flg22 had stimulated the expression of the MdFLS2 gene and its downstream target genes. Furthermore, the ectopic expression of MdFLS2 complemented the function of the Arabidopsis fls2 mutant and conferred enhanced flg22 tolerance to the transgenic Arabidopsis, suggesting that MdFLS2 acts as a positive regulator in the response to pathogens in apple.